Strengthening Local Food Security Through Analysis of The Impact of The Pumped Irrigation Program In Lebak Regency - Dedi Wahyudin; Riswanda Riswanda; Riny Handayani (Eduvest - Journal of Universal Studies, 2025)
This study aims to evaluate the implementation of the Pumped Irrigation Program in Lebak Regency, Banten, and its impact on food security. The agricultural sector in Lebak faces significant challenges, including suboptimal productivity and high dependence on rainfed land, which threatens regional food security. This study uses an evaluative qualitative approach with a six-criteria framework from William N. Dunn (effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy) to conduct a comprehensive analysis. Data were collected through in-depth interviews with key stakeholders, participatory observations, as well as analysis of program documents and statistical data. The results revealed a significant "implementation deficit", where the program's potential was hampered by systemic weaknesses. Despite demonstrating local effectiveness in improving crop indexes, the overall impact is hampered by operational inefficiencies, inadequate resource allocation, uneven distribution of aid, and lack of responsiveness to local needs. It was found that there are critical socio-technical discrepancies, where the provision of technology is not supported by human capacity building and adequate institutional support. The study concludes that the program's contribution to food security is still suboptimal due to the failure of the implementation. Policy recommendations are focused on strengthening monitoring and evaluation systems, implementing data-based and participatory targeting, integrating technical training with technology distribution, and developing sustainable operational models.